Tocilizumab as a first line biologic agent in rheumatoid arthritis patients with inadequate response to disease-modifying antirheumatic drugs: real life experience from the TReasure Registry - Karadag, O.; Farisogullari, B.; Yagiz, B.; Erden, A.; Ademoglu, Z.; Kimyon, G.; Kalyoncu, U. (Clinical & Exper Rheumatology, 2024)
Objective To evaluate the retention rate, treatment response and safety of tocilizumab (TCZ) as first-line biologic treatment in rheumatoid arthritis (RA) patients with inadequate response to disease-modifying anti-rheumatic drugs (DMARD-IR). Methods The TReasure Registry is a multicentre, web-based registry of RA and spondyloarthritis patients across Turkey. DMARD-IR RA patients who received TCZ as first-line biologic treatment were included in this registry for efficacy and safety. Demographic and clinical data, treatments, and adverse events were collected. Drug retention rate was estimated using Kaplan-Meier analysis. Results Among 642 RA patients who ever used TCZ, 258 DMARD-IR RA patients (male/female: 18.2%/81.8%, mean age, 54.41 years) received TCZ as first-line biologic. The median disease duration was 97 (range, 60-179) months and the median TCZ treatment duration was 15 (range, 6-28) months. At the 6th and 12th months of TCZ treatment, the decrease in disease activity scores from baseline was significant. The Kaplan-Meier analysis revealed the retention rate of TCZ at the 12th, 24th, 36th, and 60th months as 81.1%, 73.8%, 66.2%, and 63.6%, respectively. Fifty-seven (22%) patients discontinued TCZ; the main reason being primary or secondary inefficacy (n=29). Conclusion Over 80% drug retention rate at 12th month of TCZ treatment in this real-world study was concordant with previously conducted TCZ clinical studies. Significant reductions not only in the disease activity score-28 but also in the simplified disease activity index (SDAI) and clinical disease activity index (CDAI) scores, along with health assessment questionnaire (HAQ) scores, supported the impact of TCZ in RA management with a good safety profile.
Keywords: tocilizumab; biological drugs; rheumatoid arthritis; drug retention; real life data